Management and Treatment for Cerebral Palsy in Children - S, Padmakar; Kumar, K Sujan; Parveen, S (Indian Journal of Pharmacy Practice)
‘Cerebral’ – refers to the brain. ‘Palsy’ – can mean weakness or paralysis or lack of muscle control. Therefore, cerebral palsy is a disorder of muscle control which results from some damage to part of the brain. Cerebral palsy (CP) is a group of permanent disorders of the development of movement and posture, causing activity limitation, that are attributed to non-progressive disturbances that occurred in the developing foetal or infant brain. The motor disorders of cerebral palsy are often accompanied by disturbances of sensation, perception, cognition, communication, and behaviour, by epilepsy, and by secondary musculoskeletal problems. Approximately 80% to 90% of children with cerebral palsy have spastic cerebral palsy. The diagnosis of spasticity in children with CP requires a complete physical examination, with ancillary testing as needed. The aim of treatment is to encourage the child to learn to be as independent as possible. Some children who have mild cerebral palsy will not have any problems in achieving independence. For others, it will be a slow process. In some with severe difficulties, considerable assistance from others will always be needed. Specific treatment varies by individual and changes as needed if new issues develop. In general, treatment focuses on ways to maintain or improve a person’s quality of life and overall health. The goal of management of cerebral palsy is not to cure or to achieve normalcy but to increase functionality, improve capabilities, and sustain health in terms of locomotion, cognitive development, social interaction, and independence.
Keywords: Cerebral palsy; Management; Treatment; Children.